Bruce - Carlin, Peter Ames. (New York : Simon & Schuster, 2012)
"... a stunning biography of Bruce Springsteen describing his life and work in vivid intimate detail"--Publisher's description.
The Gut Bomb King -- The place I loved the most -- A new kind of man -- As my mind bends clouds into dreams -- Oh geez, let's make a band -- Break out the guns and ammo, everything's gonna be just fine -- For personal reasons this has to be my last song -- Somebody else who was a little crazy in the eyes -- Now I wanna see if you've got any ears -- I am finally, finally, where I'm supposed to be -- Listen to your junk man ... he's singing -- Hyperactivity was our business -- Then again, let's just let it ride -- A classic case of be careful what you wish for -- It was me and you, Baby, I remember the night you promised -- There's always room to throw something out -- Big man! Are they still standing? -- That's your time clock, my friend -- Deliver me from nowhere -- The blue- collar troubadour -- Smilin' kind of funny, everybody happy at last -- I didn't even know the language of partnership -- Get the hostility out now, I can take it -- Holy shit, I'm back -- Hope, dreams, and rededication -- The country we carry in our hearts is waiting -- That's a big shark, man -- The next stand of trees.
"A Touchstone book."
Includes bibliographical references (p. [465]-467) and index.
Keywords: Springsteen, Bruce; Rock musicians -- United States -- Biography